A stable film-forming gel polymer electrolyte, its preparation method, and its application.

By using a copolymer frame formed by copolymerizing acrylate monomers containing a mesh crosslinked structure and chain acrylate monomers in sodium metal batteries, combined with a phenylboric acid additives, the problem of poor interface compatibility of gel polymer electrolytes is solved, and stable SEI/CEI film formation and improved performance of sodium metal batteries are achieved.

CN116581374BActive Publication Date: 2025-04-29CENT SOUTH UNIV +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310305914.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-27
Publication Date
2025-04-29
Estimated Expiration
2043-03-27

AI Technical Summary

Technical Problem

The existing gel polymer electrolytes have poor interfacial compatibility in sodium metal batteries, resulting in battery capacity decay and safety problems, and it is difficult to build a stable cathode/electrolyte interface (CEI) and solid electrolyte interface (SEI) layers.

Method used

A copolymer frame formed by in-situ copolymerization reaction of acrylate monomer containing a network crosslinked structure and a chain acrylate monomer is used to form a stable film-forming gel polymer electrolyte.

Benefits of technology

This electrolyte can form a uniform and dense SEI/CEI film during the charge and discharge process, which improves the cycle stability and electrochemical performance of sodium metal batteries, reduces the formation of negative electrode sodium dendrites and dead sodium, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116581374B_ABST
    Figure CN116581374B_ABST
Patent Text Reader

Abstract

The present invention discloses a gel polymer electrolyte with stable film formation, which relates to the technical field of gel polymer electrolytes. The gel polymer electrolyte is composed of a copolymer framework, an additive, a sodium salt, and an organic solvent. The copolymer framework is a polymer obtained by in-situ copolymerization of an acrylate monomer containing a network cross-linking structure and a chain acrylate monomer. The electrolyte of the present invention has a relatively high oxidation decomposition voltage and can form a uniform and dense SEI / CEI film during the charge and discharge process. The present invention also provides a preparation method of the polymer electrolyte and an application of the polymer electrolyte in preparing a sodium metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gel polymer electrolytes, and more particularly to a stable film-forming gel polymer electrolyte and a preparation method and application thereof. Background Art

[0002] With the advancement of science and technology and the rapid development of human society, the total demand for energy is growing exponentially. According to the current energy usage, coal, oil, and natural gas will all be exhausted around 2050, so environmentally friendly and almost inexhaustible renewable energy such as solar energy has come into the sight of researchers. However, due to the limitations of natural conditions, most renewable energy is uneven and discontinuous in time and space, and cannot be directly input into the power grid. Large-scale energy storage equipment with good safety and low cost is needed as a medium to adjust the distribution of new energy.

[0003] The widely used lithium-ion batteries are limited by the limited reserves of lithium, which is only 0.006% in the earth's crust. The high price makes it difficult to expand into the large-scale energy storage industry. Sodium-ion batteries, which have similar properties to lithium-ion batteries and are lower in cost, are ideal alternatives. In order to avoid the safety issues caused by traditional liquid electrolytes and retain high conductivity, gel polymer electrolytes have been used in the preparation of sodium metal batteries. However, the gel electrolytes in sodium metal batteries have poor interfacial compatibility and are easily oxidized and decomposed violently on the surface of the positive electrode, releasing gases such as CO and CO2, and forming an unstable positive electrode / electrolyte interface (CEI), which increases the interfacial impedance between the positive electrode / electrolyte interface and causes battery capacity decay. Secondly, the higher cut-off voltage will promote the reaction between the sodium metal negative electrode and the organic electrolyte, thereby producing an unstable solid electrolyte layer (SEI), resulting in the consumption of the electrolyte and a rapid decrease in the Coulombic efficiency (CE). In addition, the dissolution of transition metals in the positive electrode material during the cycle degrades the positive electrode structure and precipitates as metal dendrites at the negative electrode, which may penetrate the diaphragm, causing short circuits and serious safety issues. Therefore, the key to improving the performance of sodium metal batteries is to develop a new type of electrolyte with good interface compatibility, high voltage and long life, to build a stable cathode / electrolyte interface (CEI) layer and solid electrolyte interface (SEI) layer, and to inhibit the side reactions between the electrode / electrolyte interface. In the prior art, the modification of gel polymer electrolytes is mostly focused on the mixing of multiple cross-linking agents and the incorporation of inorganic electrolytes, which still cannot completely solve the problem of poor interface compatibility of gel electrolytes.

[0004] Therefore, according to the above, providing a gel polymer electrolyte with stable film formation and a preparation method and application is a technical problem that technicians in this field urgently need to solve. Summary of the invention

[0005] In view of this, the present invention provides a gel polymer electrolyte with stable film formation, which has a high oxidation decomposition voltage and can form a uniform and dense SEI / CEI film during the charge and discharge process; the present invention also provides a method for preparing the polymer electrolyte and its application in preparing sodium metal batteries.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] A gel polymer electrolyte with stable film formation is composed of a copolymer framework, an additive, a sodium salt and an organic solvent. The copolymer framework is a polymer obtained by in-situ copolymerization of an acrylate monomer containing a network cross-linking structure and a chain acrylate monomer; the additive is a phenylboric acid additive; the sodium salt is one or more of NaPF6, NaClO4, NaFSI, NaTFSI and NaBF4; the organic solvent is one or more of ester solvents selected from propylene carbonate PC, ethylene carbonate EC, ethyl methyl carbonate EMC, dimethyl carbonate DMC and diethyl carbonate DEC, and one or more fluorinated ester solvents, wherein the fluorinated ester solvent is FEC, FEMC, FDMC and FDEC, wherein the fluorinated ester solvent accounts for 2% to 40% of the total solvent volume ratio.

[0008] Preferably, the acrylate monomer containing a network cross-linked structure is selected from one or both of ethoxylated trimethylolpropane triacrylate and trimethylolpropane triacrylate; the chain acrylate monomer is selected from one or more of acetoacetoxyethyl methacrylate, methyl methacrylate, ethyl acrylate, and acrylate; the mass ratio of the acrylate monomer with a network cross-linked structure to the chain acrylate monomer is 1:(0.2-10).

[0009] Preferably, the structural formula of the additive is as shown in the following formula (I):

[0010]

[0011] Wherein R1-R5 is selected from one or more of H, halogen, alkyl, alkoxy, benzene ring, C1-C6 straight chain or branched alkyl substituted by halogen.

[0012] Preferably, the composition calculated by mass percentage is: 1% to 10% of copolymer framework, 0.01% to 5% of additives, 5% to 20% of sodium salt, and 60% to 85% of organic solvent.

[0013] A method for preparing the above-mentioned stable film-forming gel polymer electrolyte specifically comprises the following steps:

[0014] S1, in an environment with a protective atmosphere and an oxygen content and a water content of less than 1ppm, weigh the raw materials in proportion, configure the organic solvent and the sodium salt into an electrolyte solution, and then dissolve the additive in the electrolyte solution. After fully dissolved, add the acrylate monomer with a network cross-linked structure and the chain acrylate monomer respectively. After fully dissolved, add a free radical initiator, and the mass percentage of the free radical initiator is ≤ 2% of the total mass of the acrylate monomer with a network cross-linked structure and the chain acrylate monomer to obtain a gel polymer electrolyte precursor solution;

[0015] S2, dripping the gel polymer electrolyte precursor solution obtained in step S1 onto the surface of the porous support material, leaving it to stand for 1-24 hours, and reacting it at 30-80° C. for 0.5-24 hours to obtain a gel polymer electrolyte.

[0016] An application of a stable film-forming gel polymer electrolyte, applied to a sodium metal battery, the sodium metal battery comprising a positive electrode plate, a negative electrode plate, an electrolyte and a shell, the electrolyte adopts the above-mentioned stable film-forming gel polymer electrolyte, the positive electrode plate is formed by mixing an active material, a conductive agent carbon black, and a binder polyvinylidene fluoride in a weight ratio of 8:1:1 to form a positive electrode slurry, which is coated on a positive electrode current collector Al foil; the active material is selected from a chemical formula P2 type positive electrode Na 0.67 TMO2(Na 0.67 Li x TMO2), O3 type positive electrode NaTMO2 or phosphate positive electrode Na3TM2(PO4)3, wherein TM is a transition metal element; and the negative electrode plate is a metallic sodium plate or an alloy sodium plate.

[0017] Preferably, the preparation method of the sodium metal battery is: in an environment with a protective atmosphere and a water content and an oxygen content of less than 1 ppm, a positive electrode plate, a negative electrode plate and a porous support material are encapsulated in a battery shell, and the gel polymer electrolyte precursor solution obtained in the above step S1 is injected into the battery shell, and the solution is allowed to stand for 1-24 hours, and reacted at 30-80° C. for 0.5 hours to 24 hours to obtain a gel polymer electrolyte, and finally a polymer gel electrolyte sodium metal battery is obtained.

[0018] The beneficial effects of the present invention are as follows:

[0019] 1. The present invention selects acrylate monomers containing a network cross-linked structure and a chain acrylate monomer. This specific monomer compound is copolymerized to form a 3D polymer cross-linked network, while improving the cross-linking efficiency, high voltage resistance, ion conductivity, and ion migration number of the polymer electrolyte; and the polymer electrolyte has a certain mechanical strength, which can reduce the formation of negative electrode sodium dendrites and dead sodium, and is suitable for high energy density and high voltage sodium metal batteries.

[0020] 2. The introduced phenylboric acid additives can preferentially form strong BO and BF bonding components on the surface of the positive / negative electrodes, construct a dense CEI / SEI film with organic matter as the base and inorganic matter evenly dispersed, inhibit the dissolution of transition metals at the positive electrode, the formation of sodium dendrites at the negative electrode, and the erosion of the positive and negative electrodes by the electrolyte, thereby improving the cycle stability of the battery.

[0021] 3. The synergistic effect of phenylboronic acid and copolymer framework can reduce the problem of unstable coulombic efficiency caused by the high reactivity of additives, improve the excessive consumption of negative electrode sodium metal, increase the cycle life of sodium metal batteries, and reduce the amount of negative electrode sodium metal.

[0022] 4. Compared with other gel polymer electrolyte technology solutions, such as using vinylidene fluoride as a crosslinker, the polymerization conditions are relatively harsh, it is difficult to achieve in-situ polymerization, and the interface compatibility is poor. However, the polymerization conditions of the crosslinker used in the present invention are mild, and the viscosity of the prepolymer solution is similar to that of the liquid electrolyte, which can completely wet the positive and negative electrodes to obtain an excellent interface; and the assembly process is similar to the traditional liquid process, and the in-situ polymerized gel network does not affect other processes under large-scale production preparation.

[0023] 5. Compared with other electrolyte additives, such as carbonate additives, NaNO3, etc., although they can significantly optimize the film-forming components, the dosage is large and usually only works on one side of the positive / negative pole, and cannot take both into account. The solution of the present invention uses a small amount of phenylboric acid additives in the gel polymer electrolyte, which can form a uniform and dense CEI / SEI film on the positive / negative electrode of the battery, significantly improving the long cycle performance of the sodium metal battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0025] Figure 1 It is a comparison diagram of the long cycle performance of Example 1 and Comparative Example 1;

[0026] Figure 2 2 are LSV curves of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] Step (1): P2 type positive electrode Na 0.67 Li 0.16 Mn 0.67 Ni 0.33 O2, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in a proper amount of n-methylpyrrolidone (NMP) solvent in a weight ratio of 8:1:1 to form a uniform positive electrode slurry; and the positive electrode slurry is coated on the positive electrode current collector Al foil, and the positive electrode sheet is obtained after drying and rolling; a sodium sheet with a thickness of 0.3 to 1.0 mm is used as the negative electrode;

[0030] Step (2): in an argon protective atmosphere with an oxygen content and a water content of less than 1 ppm, 0.2 wt% 4-trifluoromethylphenylboric acid (TFPBA), 3.65 wt% ethoxylated trimethylolpropane triacrylate (ETPTA) and 1.85 wt% acetoacetoxyethyl methacrylate (AAEM) are dissolved in an electrolyte containing a sodium salt, wherein the electrolyte is 1 mol / L sodium hexafluorophosphate dissolved in a solvent of propylene carbonate, ethyl methyl carbonate and fluoroethylene carbonate in a volume ratio of 12:12:1, and after stirring for 20 minutes, 0.5 wt% of azobisisobutyronitrile as an initiator accounting for the total mass of the crosslinking agent monomer is added to the formed mixed organic solution to obtain a gel polymer electrolyte precursor solution;

[0031] Step (3): The positive / negative electrode sheets prepared in step (1) are assembled into button cells in a glove box with a water and oxygen content of less than 0.5 ppm. The battery shell model is a 2016 battery shell. The prepolymer solution prepared in step (2) is dripped onto the surface of the glass cellulose diaphragm, and the positive battery shell, positive electrode sheet, diaphragm, negative electrode sheet, and negative battery shell are stacked in order. After packaging, they are heated at 60° C. for 12 hours for in-situ polymerization to obtain a gel polymer electrolyte.

[0032] Comparative Example 1

[0033] The gel polymer electrolyte precursor solution only uses 0.2 wt% 4-trifluoromethylphenylboric acid, no crosslinking monomer is added, and the other conditions are the same as those in this embodiment to produce a button battery. The LSV curve of the battery obtained under the same test conditions is as follows: Figure 2 As shown. Figure 2It can be seen that the oxidation potential of the battery in Example 1 is increased from 4.7 V to 5.1 V compared with the original sample due to the synergistic effect of the phenylboric acid additive and the polymer framework; while the oxidation potential of Comparative Example 1 is reduced to 4.0 V due to the high reactivity of the phenylboric acid additive.

[0034] Example 2

[0035] The preparation method is basically the same as that of Example 1, except that the additive used in the electrolyte is 0.1 wt% 4-trifluoromethylphenylboric acid based on the total mass of the electrolyte.

[0036] Example 3

[0037] The preparation method is basically the same as that of Example 1, except that the additive used in the electrolyte is 0.2 wt % 2-fluorophenylboric acid (FPBA) based on the total mass of the electrolyte.

[0038] Example 4

[0039] The preparation method is basically the same as that of Example 1, except that the crosslinking agent monomers used in the electrolyte are 7.3 wt % ethoxylated trimethylolpropane triacrylate and 3.7 wt % acetoacetoxyethyl methacrylate.

[0040] Example 5

[0041] The preparation method is basically the same as that of Example 1, except that the crosslinking agent monomers used in the electrolyte are 3.65 wt % trimethylolpropane triacrylate (TMPTA) and 1.85 wt % methyl methacrylate (MMA).

[0042] Example 6

[0043] The preparation method is basically the same as that of Example 1, except that the crosslinking agent monomers used in the electrolyte are 7.3 wt % ethoxylated trimethylolpropane triacrylate and 3.7 wt % methyl methacrylate.

[0044] Example 7

[0045] The preparation method is basically the same as that of Example 1, except that the positive electrode material used in the sodium metal battery is sodium vanadium phosphate Na3V2(PO4)3, and the charge and discharge voltage range is 2.5 to 3.8V.

[0046] Example 8

[0047] The preparation method is basically the same as that of Example 1, except that the positive electrode material used in the sodium metal battery is O3-NaMn 1 / 3 Fe 1 / 3 Ni 1 / 3 O2, the charge and discharge voltage range is 2.0~4.0V.

[0048] Example 9

[0049] The preparation method is basically the same as that in Example 1, except that the negative electrode used in the sodium metal battery is an alloy sodium sheet.

[0050] Comparative Example 2

[0051] The preparation method is basically the same as that of Example 1, except that only 3.65 wt % of ethoxylated trimethylolpropane triacrylate is added to the electrolyte, and no additives or chain acrylate monomers are added.

[0052] Comparative Example 3

[0053] The preparation method is basically the same as that of Example 1, except that only 1.85 wt % of ethyl acetoacetate methacrylate is added to the electrolyte, and no additives or monomers containing a network structure crosslinking agent are added.

[0054] Comparative Example 4

[0055] The preparation method is basically the same as that of Example 1, except that only 3.65 wt % of ethoxylated trimethylolpropane triacrylate and 0.2 wt % of 4-trifluoromethylphenylboric acid additives are added to the electrolyte, and no chain crosslinking agent monomer is added.

[0056] Comparative Example 5

[0057] The preparation method is basically the same as that of Example 1, except that only 3.65 wt % of ethoxylated trimethylolpropane triacrylate and 1.85 wt % of acetoacetoxyethyl methacrylate are added to the electrolyte, and no additives are added.

[0058] Comparative Example 6

[0059] The preparation method is basically the same as that of Example 1, except that only 1.85 wt % of ethyl acetoacetate methacrylate and 0.2 wt % of 4-trifluoromethylphenylboronic acid additives are added to the electrolyte, and no monomer containing a network structure crosslinking agent is added.

[0060] The contents of the crosslinking agent monomers and additives in the electrolytes of the above-mentioned embodiments and comparative examples are shown in Table 1.

[0061] Table 1 Crosslinking agent and additives in comparative examples 1 to 6 and examples 1 to 6

[0062]

[0063] The button-type sodium metal batteries of the above-mentioned Examples 1-6 and Comparative Examples 1-6 were subjected to a 30° C. constant temperature test using the following method:

[0064] At 30°C, the sodium metal battery was charged to 4.2V (1C = 140mAh / g) at a rate of 0.2C, and then discharged to 1.8V at a rate of 0.2C, and the discharge capacity at this time was recorded as d1 (i.e., the initial discharge capacity). After 200 cycles, the discharge capacity at this time was recorded as d2. 15 sodium metal batteries were tested in each group, and the average value was taken.

[0065] The capacity retention rate of sodium metal battery at 30°C = [d2 / d1] × 100%.

[0066] The test results of initial discharge capacity and capacity retention rate at 30°C are shown in Table 2.

[0067] Table 2 Performance test results of initial discharge capacity and capacity retention rate at 30℃

[0068]

[0069]

[0070] From the performance test results of the comparative examples and embodiments in Table 2, the battery cycle performance is poor without adding phenylboric acid additives; however, when only phenylboric acid additives are added without adding crosslinking monomers, the initial specific capacity is greatly reduced due to the high reactivity and low oxidation potential window of the additives; when the gel polymer framework and the additives work together, the electrochemical performance of the battery is significantly improved. At the same time, the amount of additives added, the type of crosslinking monomers and the amount added also have a great influence on the electrochemical performance of the battery.

[0071] Phenylboric acid additives have a higher highest occupied molecular orbital (HOMO) energy level, and will be preferentially oxidized on the positive electrode surface to form a uniform and dense CEI film during the initial charging process, protecting the positive electrode material from being corroded by negative active substances (such as HF, H2O, etc.) in the electrolyte, and inhibiting the dissolution of transition metals. In addition, phenylboric acid additives can also participate in the formation of SEI film, improve the interfacial stability of the negative electrode and the electrolyte, reduce the formation of sodium dendrites, and significantly improve the electrochemical performance of the battery. 4-trifluoromethylphenylboric acid and 2-fluorophenylboric acid in the embodiment are representatives of phenylboric acid additives, and other similar structural additives also have such effects, and are also applicable to the electrolyte described in the present invention, which are not listed one by one.

[0072] The network crosslinking agent monomer has a fast crosslinking rate, and can quickly form a gel electrolyte in a short polymerization time and at a low polymerization temperature, reducing the byproducts of the electrolyte at high temperature; the chain crosslinking agent monomer has multiple sodium ion conduction sites, and has high flexibility after polymerization, and can obtain high conductivity and good interface compatibility. The two work together to improve the various performances of the gel polymer electrolyte. The ethoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate, acetoacetoxyethyl methacrylate, and methyl methacrylate in the embodiment are representative crosslinking agent monomers. Other crosslinking agent monomers with similar structures also have such effects and are also suitable for the electrolyte described in the present invention, which are not listed one by one.

[0073] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A stable film-forming gel polymer electrolyte, composed of a copolymer framework, an additive, a sodium salt, and an organic solvent, characterized in that: The copolymer framework is a polymer obtained by in-situ copolymerization of an acrylic acid ester monomer containing a network cross-linked structure and a chain acrylic acid ester monomer; the additive is a phenylboric acid additive; the sodium salt is one or more of NaPF6, NaClO4, NaFSI, NaTFSI and NaBF4; the organic solvent is one or more of ester solvents selected from propylene carbonate PC, ethylene carbonate EC, ethyl methyl carbonate EMC, dimethyl carbonate DMC and diethyl carbonate DEC, and one or more fluorinated ester solvents, wherein the fluorinated ester solvent is FEC, FEMC, FDMC, FDEC, wherein the fluorinated ester solvent accounts for 2% to 40% of the total solvent volume ratio; The acrylate monomer containing a network cross-linked structure is selected from one or both of ethoxylated trimethylolpropane triacrylate and trimethylolpropane triacrylate; the chain acrylate monomer is selected from one or more of acetoacetoxyethyl methacrylate, methyl methacrylate, ethyl acrylate, and acrylate; the mass ratio of the acrylate monomer with a network cross-linked structure to the chain acrylate monomer is 1:(0.2-10); The structural formula of the additive is shown in the following formula (I): ; (I) Wherein R1-R5 is selected from one or more of H, halogen, alkyl, alkoxy, benzene ring, C1-C6 straight chain or branched alkyl substituted by halogen.

2. A gel polymer electrolyte with stable film formation according to claim 1, characterized in that: The composition calculated by mass percentage is: 1% to 10% of copolymer framework, 0.01% to 5% of additives, 5% to 20% of sodium salt, and 60% to 85% of organic solvent.

3. A method for preparing a stable film-forming gel polymer electrolyte as claimed in any one of claims 1 to 2, characterized in that: The specific steps include: S1, in an environment with a protective atmosphere and an oxygen content and a water content of less than 1ppm, weigh the raw materials in proportion, configure the organic solvent and the sodium salt into an electrolyte solution, and then dissolve the additive in the electrolyte solution. After fully dissolved, add the acrylate monomer with a network cross-linked structure and the chain acrylate monomer respectively. After fully dissolved, add a free radical initiator, and the mass percentage of the free radical initiator is ≤ 2% of the total mass of the acrylate monomer with a network cross-linked structure and the chain acrylate monomer to obtain a gel polymer electrolyte precursor solution; S2, dripping the gel polymer electrolyte precursor solution obtained in step S1 onto the surface of the porous support material, leaving it to stand for 1-24 hours, and reacting it at 30-80° C. for 0.5-24 hours to obtain a gel polymer electrolyte.

4. Application of a stable film-forming gel polymer electrolyte in a sodium metal battery, wherein the sodium metal battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a shell, characterized in that: The electrolyte adopts the stable film-forming gel polymer electrolyte as claimed in claim 1 or 2, and the positive electrode plate is formed by coating a positive electrode slurry formed by mixing active material, conductive agent carbon black, and binder polyvinylidene fluoride in a weight ratio of 8:1:1 on the positive electrode collector Al foil; the active material is selected from the chemical formula P2 type positive electrode Na 0.67 One or more of TMO2, O3 type positive electrode NaTMO2 or phosphate positive electrode Na3TM2(PO4)3, wherein TM is a transition metal element; and the negative electrode plate is a metal sodium plate or an alloy sodium plate.

5. The use of a stable film-forming gel polymer electrolyte according to claim 4, characterized in that: The preparation method of the sodium metal battery is as follows: in an environment with a protective atmosphere and a water content and an oxygen content both less than 1 ppm, a positive electrode plate, a negative electrode plate and a porous support material are encapsulated in a battery shell, the gel polymer electrolyte precursor solution obtained in step S1 of claim 3 is injected into the battery shell, and the solution is allowed to stand for 1-24 hours, and reacted at 30-80° C. for 0.5 hours to 24 hours to obtain a gel polymer electrolyte, and finally a polymer gel electrolyte sodium metal battery is obtained.

Citation Information

Patent Citations

  • Gel polymer battery and preparation method thereof

    CN112018427A

  • Polymer solid electrolyte containing soluble additive and all-solid-state metal lithium battery

    CN115020831A